An Imitating Device for Assisting Trans-Radial Amputees using Gestures - Vishnuvarthanan Govindaraj, M Sofia Fazila,VSheickHussain Beevi, M Marikani,Thiyagarajan ArunPrasath,Saravanan Alagarsamy (International Journal of Advanced Science and Technology, 2020)
A prosthetic arm is an artificial device which mainly focuses on mimicking the functioning and activities of the human forearm for facilitation of their Activities of Daily Living (ADLs). This paper aims to capture the hand gesture or representation actions to actuate the prosthetic limb of trans-radial amputees. The approach mainly focuses on the hand gesture of contralateral arm, instead of physiological signals. The two phases involved in this process include gesture sensing phase and motion phase. Initially, during the gesture sensing phase, images are captured using proximity sensor and orientation sensor of 1SHEELD mobile application. This tracks the motion and gesture of the contralateral arm. Motion phase includes servo motors which are controlled by Arduino UNO using Embedded C codes. Once a particular gesture is captured, the input signals are given to 1SHEELD+ board where template matching and gesture recognition takes place through predefined algorithms. After successful gesture recognition, the servo motors are driven by Arduino UNO Microcontroller. This initiates movement in the prosthetic limb. The major theme of the paper is to provide an affordable and easily operable device for the ease of convenience of the trans-radial amputees. This helps the amputees to carry out their day-to-day activities by themselves in a sustainable manner. Antecedent to this approach, they have used software coding to track the articulations of hand and finger for supporting the motions of robotic arm, which is attached to the exoskeletal structure of the human hand. In our proposed methodology, we use 1SHEELD+ board for inducing movements in trans-radial amputees.